Textiles and Cult in the Ancient Mediterranean - Brøns, Cecilie (Ancient Textiles Ser, 2017)
"Frontcover" -- "Title " -- "Copyright" -- "Contents" -- "List of contributors" -- "Preface" -- "Part I Greece" -- "1 Offering of cloth and/or clothing to the sanctuaries: A case of ritual continuity from the 2nd to the 1st millennium BCE in the Aegean?" -- "2 What does the clothing say about the killer? Some thoughts on textiles in depictions of sacrifice in Archaic Athens" -- "3 Not nothing: Conceptualising textile whiteness for cult practice" -- "4 Weaving the Chalkeia: Reconstruction and ritual of an Athenian festival" -- "5 Dress, code and identity-of-place in Greek religion: Some cases from Classical and Hellenistic Athens" -- "6 Priestly dress in the ancient Mediterranean: Herodotus as a source-book" -- "7 Headdress for success: Cultic uses of the Hellenistic mitra" -- "8 Astral symbols on a loom weight from Adjiyska Vodenitsa (ancient Pistiros), Thrace: Measurement, astronomy, and cult" -- "Part II Italy" -- "9 Building V and ritual textile production at Timpone della Motta" -- "10 The loom weights from the âScarico di Grotta Vanellaâ: Evidence for a sanctuary on the north acropolis of Segesta?" -- "11 Loom weights in sacred contexts: The Square Building of the Heraion near the Sele River" -- "12 âTemple keyâ or distaff? An ambiguous artefact from the Greek and indigenous sanctuaries of southern Italy" -- "13 On priests, priestesses, and clothing in Roman cult practices" -- "Part III The Levant and the Near East" -- "14 Textiles in Assyrian and Babylonian temples from the 1st millennium BCE" -- "15 Textile production in the Neo-Babylonian Eanna archive" -- "16 The description of AnÄhitÄâs attire in the YaÅ¡t 5" -- "17 Modes of textile production in cultic contexts in the Iron Age Southern Levant: The finds from Tell eá¹£-á¹¢Ã¢fÄ«/Gath".